Developing Small Scale Flare Gas Recovery Unit To Utilize Not Economically Feasible Gas Flare - Yusep K Caryana (Scientific Contributions Oil and Gas, 2009)
The World Bank’s flare gas utilization evaluation in Indonesia (2006) excluded the not economically feasible flare gas to be commercially utilized due to various barriers and economic reasons. To implement No Flare Gas Policy in Indonesia, it is necessary to carry out an analysis on the possibility of the not economically feasible flare gas based on the latest technology development and proximity flare gas market next to existing onshore oil/gas fields producing the flare gas. Small Scale Flare Gas Recovery Unit has been modelled to recover the gas flared and transported the gas to the proximity flare gas market. This concept shows that the not economically feasible flare gas can be commercially utilized in term of small/medium bussiness unit, and therefore No Flare Gas Policy in Indonesia will be achieved.